Propuesta de mejora al sistema logístico de Homecenter Villavicencio en el área de despacho y entrega de mercancía. (2020)
The main objective of this research proposal is to aim alternatives for the logistics system improvement at Homecenter Villavicencio; using the SCOR model which is characterized by measuring the performance of logistics processes throughout the supply chain. The first procedure is focused on identifying the current state of logistics processes, where it seeks to establish the shortcomings that occur in the involved areas and how to improve them. Afterwards, the efficiency attributes and metrics are measured for each level as established by the SCOR model, taking into account the information obtained, the best practices applicable to each process or attribute are selected. Lastly, as the central axis is the action plan aimed at improving the receipt and delivery processes, among others. Which the proper development of processes is intended to be efficient and organized that constitute mutual benefit for the company and customers, generating a higher satisfaction rate. Finally, the proposal will make it possible to contribute to the development and continuous improvement of logistics processes, in the same way, obtain a higher performance in management indicators, generating a positive impact at the general level of the store.